Determinantes da adoção de práticas e tecnologias de agricultura de precisão por fornecedores de cana-de-açúcar no estado de São Paulo - Mozambani, Carlos Ivan (Universidade Federal de São Carlos, 2021)
The following thesis identifies and analyzes the determinants of the adoption and the intensity of adoption of precision agriculture technologies (PATs) by sugarcane suppliers in the state of São Paulo, Brazil, as well as the main barriers to adoption. In person interviews with 131 sugarcane farmers provided cross-sectional farm level data from the 2018/19 crop year. The farmers were interviewed using a semi-structured questionnaire and the primary data were analyzed by means of descriptive statistics, hypothesis test and count data models. Six PATs adopted by the farmers were identified: GNSS and images for rows planning; tractor/harvester with automatic guidance system; georeferenced grids for soil sampling; images (satellite and/or ARP) for mapping pest and yield; variable rate application of fertilizers; and variable rate application of pesticide. The adoption and adoption intensity (dependent variable) were measured as the number of PATs used by farmers. Fifty-three farmers adopted at least one of these technologies, while 78 farmers did not. The results show that the agricultural information provided by the sugarcane mill, the farm size, as well as the perception of increased productivity are factors that positively and significantly influence the farmer’s decision of adoption PATs. The access to technical assistance information, the participation in agricultural events (workshop, farms fair and farm field days), the farmer’s previous experience, the availability of credit and the perception of increased productivity positively impact the decision to adopt a greater number of PATs, that is, the adoption intensity of the PATs. The adopters indicated that they had faced difficulties related to the connectivity in the field, the lack of technical assistance from equipment suppliers, the lack of trained labor and the incompatibility of the communication interface between computer systems of different agricultural equipment as the main barriers to adoption. For the non-adopters, the main barriers for adoption were the high initial investment.
Determinants of the adoption of precision farming practices and technologies by sugarcane suppliers in the state of São Paulo
Keywords: Cana-de-açúcar; Adoção de tecnologia; Intensidade de adoção; Agricultura de Precisão; Poisson com zero inflado; Sugarcane; Adoption of technology; Adoption intensity; Precision agriculture; Zero-Inflated Poisson (ZIP); CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO; CIENCIAS SOCIAIS APLICADAS::ECONOMIA